Legal Protection for Indigenous Peoples of Early Sundan (Sunda Wiwitan): A Case Study of Discrimination Against Religious Status in Cigugur, Kuningan - Azzahra, Nanda; Gunawan , Roby; Yunita , Yunita; Permana , Deni Yusup; Dikrurahman, Diky (Journal of Legal and Cultural Analytics, 2025)
Sunda Wiwitan is an indigenous belief system of the Sundanese people, still practiced today, particularly in the Kanekes region. Its adherents often face discrimination in legal and social aspects, such as difficulties in administrative documentation, access to public services, and religious recognition. These challenges affect their social status in society. This study aims to analyze the forms of discrimination experienced and evaluate the effectiveness of legal protection provided by the state. The research uses a juridical-empirical approach, examining the effectiveness of legal norms through social realities. The findings reveal that, although legal frameworks exist to recognize indigenous beliefs, their implementation has not fully ensured fair protection. Therefore, regulatory enhancement and public education are necessary to improve the social status and guarantee the constitutional rights of Sunda Wiwitan adherents as equal citizens.